1996
DOI: 10.1111/j.1600-0765.1996.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation endproducts (AGEs) induce oxidant stress in the gingiva: a potential mechanism underlying accelerated periodontal disease associated with diabetes

Abstract: We hypothesized that one mechanism underlying advanced periodontal disease in diabetes may involve oxidant stress in the gingiva, induced by the effects of Advanced Glycation Endproducts (AGEs), the irreversible products of non-enzymatic glycation and oxidation of proteins and lipids which accumulate in diabetic plasma and tissue. Infusion of AGE albumin, a prototypic ligand, into mice resulted in increased generation of thiobarbituric acid reactive substances (TBARS) compared with infusion of non-glycated alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
188
1
13

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(213 citation statements)
references
References 49 publications
8
188
1
13
Order By: Relevance
“…A associação entre cárie com obesidade/sobrepeso tem mostrado uma forte ligação com condição socioeconômica, uma vez que a urbanização e o crescimento econômico alteram de forma significativa Diversas são as teorias que buscam explicar essa positiva associação entre a obesidade e as doenças periodontais. Recentes estudos sugerem uma associação entre a obesidade e o sistema imune, enquanto que a primeira prejudica a ação efetiva do sistema imune corporal 25 . Esse fator é de suma importância quando se procura entender a ligação entre sobrepeso e doença periodontal, ambas classificadas como doenças crônicas não transmissíveis.…”
Section: Revisão De Literaturaunclassified
See 2 more Smart Citations
“…A associação entre cárie com obesidade/sobrepeso tem mostrado uma forte ligação com condição socioeconômica, uma vez que a urbanização e o crescimento econômico alteram de forma significativa Diversas são as teorias que buscam explicar essa positiva associação entre a obesidade e as doenças periodontais. Recentes estudos sugerem uma associação entre a obesidade e o sistema imune, enquanto que a primeira prejudica a ação efetiva do sistema imune corporal 25 . Esse fator é de suma importância quando se procura entender a ligação entre sobrepeso e doença periodontal, ambas classificadas como doenças crônicas não transmissíveis.…”
Section: Revisão De Literaturaunclassified
“…Mesmo diante da descoberta de que a obesidade acomete a imunidade, levando o indivíduo a tornar--se mais propício ao desenvolvimento de doenças periodontais 25 , outros fatores ainda são dúvidas de pesquisadores que procuram entender a relação entre essas duas doenças, como a maior ingestão de açúcares, escovação inadequada e diminuição de secreção salivar em obesos, entre outros.…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation
“…Elevated glucose concentrations induce non-enzymatic glycation and oxidation of proteins like collagen, and lipids, resulting in the accumulation of advanced glycation end products (AGEs) in diabetic tissues [2]. AGEs interact with their receptors present on the cell surface called the receptor for AGE (RAGE), bringing about various pathological changes.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that diabetes is associated with oxidative stress and ROS [9,[21][22][23][24][25][26][27]. Increased ROS generation has been found in diabetic rats [28], and it has been determined that there is excessive oxidative stress in pregnancies complicated by diabetes [5], which may be lessened by anti-oxidants [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%